The Influence Of Financial Literacy And Digital Literacy On The Income Of Boueqet Msme Actors In Pajus Market, Medan - Najwa Syahfitri; Maya Macia Sari; Noni Ardian (Journal of Management, Economic, and Accounting, 2026)
This study aims to analyze the effect of financial literacy and digital literacy on the income of MSME bouquet entrepreneurs in Pajus Market, Medan. The study uses a quantitative associative approach with a sample of 30 MSME entrepreneurs determined through saturated sampling technique. Primary data were obtained through questionnaires and tested using multiple linear regression analysis with the help of SPSS. The results showed that financial literacy had a significant effect on MSME income, as evidenced by a partial test with a significance value of 0.031. Digital literacy was also found to have a significant effect with a significance value of 0.001. Simultaneously, both independent variables had a significant effect on income, with a coefficient of determination of 0.603, meaning that 59.3% of income variation could be explained by financial literacy and digital literacy. These findings confirm that increasing the financial literacy and digital literacy capacity of MSME actors is a crucial factor in improving competitiveness and increasing business income in the digital era.